2018
DOI: 10.1177/0340035218763445
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of knowledge sharing behaviour on Sustainable Development Goals among library personnel in Nigeria

Abstract: The study was carried out to investigate the predictors of library personnel’s knowledge sharing behaviours and its implication for achieving sustainable development goals, using the theory of planned behaviour. Survey research design was adopted for the study whereby a structured questionnaire was used to elicit data from 100 registered library personnel in Anambra State, Nigeria. Total enumeration was adopted as the sampling technique to obtain the population sample. The study revealed that attitude, perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Conversely, organizational knowledge-rejecting norms might hinder KSB (Husted and Michailova, 2002). Although some studies have questioned the relationship between SN and KSI (Sihombing, 2011;So and Bolloju, 2010;Zhang and Ng, 2012;Ling et al, 2013), notable number of researchers have reported the significant positive relationship between both constructs (Ryu et al, 2003;Lin and Lee, 2004;Bock et al, 2005;Stenius et al, 2015;Mafabi et al, 2017;Igbinovia, 2018). Based on the mentioned findings, the following hypothesis is derived: H2.…”
Section: Attitude Toward Knowledge Sharingmentioning
confidence: 94%
“…Conversely, organizational knowledge-rejecting norms might hinder KSB (Husted and Michailova, 2002). Although some studies have questioned the relationship between SN and KSI (Sihombing, 2011;So and Bolloju, 2010;Zhang and Ng, 2012;Ling et al, 2013), notable number of researchers have reported the significant positive relationship between both constructs (Ryu et al, 2003;Lin and Lee, 2004;Bock et al, 2005;Stenius et al, 2015;Mafabi et al, 2017;Igbinovia, 2018). Based on the mentioned findings, the following hypothesis is derived: H2.…”
Section: Attitude Toward Knowledge Sharingmentioning
confidence: 94%
“…(156) Instead, Kabamba and others (e.g. Igbinovia, 2016;Igbinovia & Osuchukwu, 2018) suggest that libraries solicit the skills and means of library schools, library associations, and development organizations to overcome challenges of capacity. This solution, however, still requires that groups such as development organizations want to work with African libraries as partners.…”
Section: African Libraries In Developmentmentioning
confidence: 99%
“…Yet, KM is still not adequately supported in academic libraries (Koenig and Scovetta, 2015). In light of this, several studies - Awodoyin et al (2016); Dey and Mukhopadhyay (2018); Daniel (2015); Borteye et al (2010); Igbinovia and Osuchukwu (2018); Akparabore (2013); Kumaresan and Swrooprani (2013); Ajegbomogun and Diyaolu (2018); Muchaonyera (2015); Onifade (2015); Parirokh et al, (2008); Aharony (2011); Lekay (2012); Chitumbo and Kanyengo (2017) using various constructs/models/paradigms/method of data collection focus on the importance of KS in libraries and seeking to identify the challenges to knowledge sharing to improve best practices.…”
Section: Introductionmentioning
confidence: 99%
“…At the organizational level, the findings from identified literature have shown that KS within a department or organization can be a function of its management and organizational culture. Library's management and culture have been identified as a factor that impedes KS (Burnette, 2017) in terms of lack of communication and social interaction between departments to foster networking (Mayekiso, 2013;Igbinovia and Osuchukwu, 2018); lack of well-defined models, policies, strategies, formal forums (in forms of meetings, seminars, workshops, etc.) to harness staff expertise (Muchaonyerwa, 2015;Mayekiso, 2013;Chitumbo and Kanyengo, 2017;Onifade, 2015;Bortoye et al, 2010;Lekay, 2012); lack of organizational and top management support in providing office layout that encourages sharing, availability of ICT infrastructure due to budget constraints (Muchaonyerwa, 2015;Kumaresan, 2010); lack of trust in organizations' management in terms of job security (Aharony, 2011;Biranvand et al, 2015;Burnette, 2017;Muchaonyerwa, 2015); staff turnover (Muchaonyerwa, 2015;Chitumbo and Kanyengo, 2017); no reward system, incentive or motivation to share (Lekay, 2012;Aharony, 2011;Igbinovia and Osuchukwu, 2018;Onifade, 2015;Kumaresan, 2010;Mayekiso, 2015); no mentoring practice or community of practice (Onifade, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation